Charles Dickens : an introduction - Hartley, Jenny (Oxford University Press, 2016)
In this short book, the author explores the key themes running through Dicken's body of work, and considers how his writing reflects his attitudes towards the harsh realities of the ninteenth-century society and it institutions.